Can I be your safe haven and secure base? A parental perspective on parent-child attachment in young children with a severe or profound intellectual disability. (October 2019) - Vandesande, Sien; Bosmans, Guy; Maes, Bea
Abstract: Background: The general developmental as well as the disability specific literature has stressed the crucial influence of parents on their child's social-emotional development. Attachment theory provides a framework to describe parental roles within the parent-child attachment relationship. The current study explored parents' perspectives on their role as attachment figure and the preconditions they consider necessary to establish secure attachment in children with severe or profound intellectual disability (ID). Methods: Semi-structured interviews with 54 parents on their child's social-emotional development, attachment behaviour and the parent-child attachment bond were analysed using the Framework Method. All children were between 15 months and seven years old and had a severe or profound ID. Results: Parents reported their child's clear preference towards them and acknowledged the role they fulfil as stress regulator. Children differed in the extent to which they use their parent to explore new environments. Overall, parents described the attachment relationship with their child as positive but challenging. Conclusions: Parents acknowledged the roles they fulfil both as a safe haven for their child, and (to a lesser extent) as a secure base. Clinical practice could benefit from a parental perspective to identify particular challenges parents encounter in building a secure attachment relationship.